The Impact of the Effectiveness of Smart Quality Management on the Profitability Enterprises of Major Asian Companies - Kareem, Jasim Mohammed (South Asian Journal of Social Sciences and Humanities, 2024)
This study aims to identify the extent of the influence of smart quality management practices and their impact on the profitability performance of major Asian companies. This paper used a sample of 143 major companies for the purpose of testing the relationship from the years 2020 to 2023. The study concluded that there is a positive and important link among smart quality management and profitability performance. Smart quality management is considered important in modern concepts that represent a new technical method for managing business processes and institutions in general. Smart quality management aims to improve profitability and productivity. This study considers smart quality management to be an integrated management system that aims to improve the firm’s reputation and growing its profits and market share, and then confirm its existence and link in the field of effort.